2022
DOI: 10.3390/w14233886
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Model Calculations of Ice Thickness with the Observations on Small Water Bodies in Katowice Upland (Southern Poland)

Abstract: Small bodies of water in densely populated areas have not yet been thoroughly studied in terms of their ice cover. Filling the existing research gap related to ice cover occurrence is therefore important for identifying natural processes (e.g., response to climate warming and water oxygenation in winter), and also has socio-economic significance (e.g., reducing the risk of loss of health and life for potential ice cover users). This paper addresses the issue of determining the utility of two simple empirical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Grouping water bodies using advanced statistical tools will enable applying the results of the study to the members of the identified groups, of which only several select water bodies were included in the ice thickness forecasting process. Thus, forecasting the ice thickness of individual bodies of water-usually tedious and requiring verification of empirical data in the field [61]-can be successfully replaced by an alternative method of assessing the ice regime of lakes, identified using the presented methodology. There is also a practical dimension to the use of statistical methods in ice regime studies: the acquired information allows for the elimination of water bodies that pose a risk of drowning from use.…”
Section: Discussionmentioning
confidence: 99%
“…Grouping water bodies using advanced statistical tools will enable applying the results of the study to the members of the identified groups, of which only several select water bodies were included in the ice thickness forecasting process. Thus, forecasting the ice thickness of individual bodies of water-usually tedious and requiring verification of empirical data in the field [61]-can be successfully replaced by an alternative method of assessing the ice regime of lakes, identified using the presented methodology. There is also a practical dimension to the use of statistical methods in ice regime studies: the acquired information allows for the elimination of water bodies that pose a risk of drowning from use.…”
Section: Discussionmentioning
confidence: 99%